EXTENSION AND TRAINING OF SNAKEHEAD FISH BREEDING AND NURSERY TECHNOLOGY IN SUNGAI BADAK VILLAGE, MESUJI REGENCY, LAMPUNG PROVINCE - Munti Sarida; Hilma Putri Fidyandini; Dorothy Rouly H. Pandjaitan (Jurnal Abdi Insani, 2023)
Pokdakan Maju Bersama Mesuji, which is in Sungai Badak Village, Mesuji District, Mesuji District, Lampung, is a group of economically productive people and potential entrepreneurs with fish farming activities in the form of growing consumption fish and local fish, especially snakehead fish. The difficult problems in the development of snakehead culture in Sungai Badak village, Mesuji Regency, are the limited availability of seeds and the slow growth of fish. These cause the business to be carried out on-off or suffer losses. This community service aims to increase the knowledge and skills of pokdakan members in producing continuous and quality snakehead seeds independently and stimulate job creation. This activity was carried out through Focus Group Discussions, and organizing counseling and training on snakehead fish hatchery technology and increasing the growth of snakehead fish with the application of recombinant growth hormone. Participants were given a written test to measure how successful the technology transfer is. The results obtained from this activity were that the knowledge and skills of the trainees increased from an average score of 58 to 85 in hatchery technology transfer (32%) and increased from an average score of 35 to 66 in the transfer of recombinant growth hormone application technology (31%) (scale 0- 100). The increase in the value of these participants is presumably because most of the participants are fish cultivators who are used to carrying out aquaculture activities but do not know the basics. So that with this activity it is hoped that it can improve the economy of cultivator families and make Mesuji Regency a fish center and support inclusive and sustainable economic growth. In general, the two technology transfers in this activity increased the percentage of participants' knowledge and skills by 31.5% and this activity was successful.